ANALISIS MANFAAT BIAYA BIOCHAR DI LAHAN PERTANIAN UNTUK MENINGKATKAN PENDAPATAN PETANI DI KABUPATEN MERAUKE - Maria Magdalena Diana Widiastuti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2016)
Biochar has been proven to increase the availability of soil nutrient, yield productivity and farmers income. Biochar can be made from forestry/agricultural waste and do not required high technology. The objective of this study were: (1) to analyze Benefit Cost Ratio (BCR) of biochar made from rice husk, (2) to compare yield productivity of paddy with biochar treatment, and (3) to analyze of paddy farming system with biochar treatment. The methodology by using BCR and productivity approach. The result showed that, firstly, the BCR of biochar from rice husks was 1.35 which indicated that biochar productivity as feasible. Secondly, the provision of biochar and fertilizer on agricultural could increase rice productivity of 4.2 ton/ha (control treatment) to 5.5 ton/ha (treatment biochar + organic fertilizer) and 6 ton/ha (treatment biochar + organic fertilizer + chemical fertilizers). Thirdly, the benefit cost ratio of paddy farming system for control treatment (1.54), higher than biochar+organic fertilizer treatment (1.46) and biochar+organic fertilizer+chemical fertilizer treatment.